Bandwidth prediction of power communication network based on DBN-Softmax - Jia LI; Li CONG; Hua JIANG; Yang HU; Meng XU (Dianxin kexue)
With the change of the power communication network,the data of the bearer service of the power communication network has increased exponentially,which puts higher requirements on the processing capability of the power communication network.In order to guarantee the service quality of communication network,aiming at the current unreasonable distribution of network bandwidth,a bandwidth prediction algorithm based on deep confidence for power communication network was proposed.The deep confidence network formed by the Boltzmann machine was used to obtain the characteristics that could perfectly express the network bandwidth,and the reasonable prediction of the bandwidth of the power communication network planning stage was realized.The implementation results show that the proposed algorithm is more accurate and robust than neural network.It has the advantage of improving the carrying capacity of the power communication network and providing a powerful guarantee for the safe and stable operation of the power system.